Rozwiązane

Potrzebna szybka pomoc.



Potrzebna Szybka Pomoc class=

Odpowiedź :

ZbiorJ

[tex]zad.a\\\\5x^{2} -6x-3x^{2} +7-x^{2} +6x=1\cdot x^{2} +0\cdot x+7\\\\5x^{2} -6x-3x^{2} +7-x^{2} +6x=x^{2} +7[/tex]

[tex]zad.b\\\\-4(-2a-3b)-2a(4-3a+2b)=8a+12b-8a+6a^{2} -4ab\\\\-4(-2a-3b)-2a(4-3a+2b)=6\cdot a^{2} +(-4)\cdot ab+0\cdot a+12\cdot b[/tex]

[tex]zad.c\\\\(4-3x)(2x+3)-5=8x^{2} +12-6x^{2} -9x-5\\\\(4-3x)(2x+3)-5=2\cdot x^{2} +(-9)\cdot x +7[/tex]

[tex]zad.d\\\\(3-2x)(4x-5)-3x(2x+1)=12x-15-8x^{2} +10x-6x^{2} -3x\\\\(3-2x)(4x-5)-3x(2x+1)=(-14)\cdot x^{2} + 19\cdot x+ (-15)[/tex]